A retrospective study on 1592 consecutively performed operations in one private referral clinic. Part II: Peri‐implantitis and implant failures. (1st March 2017) - Jemt, Torsten; Karouni, Michel; Abitbol, Jérémy; Zouiten, Ons; Antoun, Hadi
Abstract: Background: Few large‐scale follow‐up studies are reported on routine implant treatment. Purpose: To report retrospective data on peri‐implantitis and overall implant failures at one private referral clinic (effectiveness study). Materials and Methods: A total of 1017 patients were consecutively provided with 3082 implants with an anodized surface during 1592 operations between 2000 and 2011. All patients with any of four events of problems were identified; "peri‐implantitis, " "surgery related to peri‐implantitis, " "overall implant failure, " and "late implant failures." A logistic multivariate analysis was performed to identify possible factors with association to the four events. Results: "Lower jaw surgery" (HR = 3.03) and "immediate gingival grafting" at implant surgery (HR = 3.34) were factors with the highest risk associated to the two peri‐implantitis events, respectively. Risk of peri‐implantitis increased by year of inclusion from year 2000 (HR = 1.28). "Overall implant failures" were associated to "smoking" (HR = 2.11), "surgical technique" (highest for direct placement; HR = 1.67), and "type of implant" (NobelActive CC; HR = 2.48). NobelActive CC was more used in upper jaws, using immediate or one‐stage surgery with bone and mucosa grafting procedures than other implants ( P  < .05). Implants lost after first year only showed an association to "lower jaw" (HR = 2.63) and "early inflammation" (HR = 17.95). Conclusion: Peri‐implantitis seem to be associated to surgical protocols more often in the posterior lower jaw in routine practice. The problems seem to increase during the inclusion period, possibly related to increased use of direct implant placement technique and grafting protocols. Early inflammatory problems have in the previous report on the present patient group been associated to the mid‐aged patient. Overall/late implant failures were shown to be associated to earlier inflammatory problems, smoking habits, surgical technique, and treatment in the posterior lower jaw.